Three-dimensional honeycomb-like hierarchically structured carbon for high-performance supercapacitors derived from high-ash-content sewage sludge1. Issue 29 (7th August 2015) - Feng, Haobin; Zheng, Mingtao; Dong, Hanwu; Xiao, Yong; Hu, Hang; Sun, Zhongxin; Long, Chao; Cai, Yijin; Zhao, Xiao; Zhang, Haoran; Lei, Bingfu; Liu, Yingliang
<x xml:space="preserve">Abstract</x> Honeycomb-like hierarchically structured carbon was prepared and investigated as excellent electrode materials for high-performance supercapacitors.